Working lives : gender, migration and employment in Britain, 1945-2007 - McDowell, Linda, 1949- (Chichester, West Sussex : Wiley Blackwell, 2013)
Full of unique and compelling insights into the working lives of migrant women in the UK, this book draws on more than two decades of in-depth research to explore the changing nature of women's employment in post-war Britain. A first-rate example of theoretically located empirical analysis of labour market change in contemporary BritainIncludes compelling case studies that combine historical documentation of social change with fascinating first-hand accounts of women's working lives over decadesIntegrates information gleaned from more than two decades of in-dept.
Chapter1 leaving home: migration and working lives -- Gendering labour geographies and histories -- The transformation of Britain -- Post-war reconstruction, 1945-1951 -- Coming home: the heart of empire, 1948-1968 -- Years of struggle, 1968-1979 -- Privilege and inequality, 1979-1997 -- Back to the future: diversity and precarious labour, 1997-2007 -- Full circle, 1945-2007.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Women foreign workers -- Great Britain -- History -- 20th century; Women immigrants -- Employment -- Great Britain -- History -- 20th century; Women immigrants -- Great Britain -- Social conditions -- 20th century; BUSINESS & ECONOMICS -- Labor; POLITICAL SCIENCE -- Labor & Industrial Relations; Great Britain -- Emigration and immigration -- Social aspects -- History -- 20th century; Great Britain -- Emigration and immigration -- Economic aspects -- History -- 20th century; Great Britain -- Economic conditions -- 20th century; Great Britain -- Social conditions -- 1945-; Electronic books; Electronic books